(untitled) (Medical Forum Monthly, 2024)
Objective: To compare the outcomes of wound closure in breast surgery incisions by conventional suture technique versus tissue adhesive. Study Design: Randomized controlled trial study Place and Duration of Study: This study was conducted at the Department of General Surgery, Breast Unit, Liaquat National Hospital. Karachi from 23rd May 2017 to 31st January 2018. Materials and Methods: Total 100 patients were included and divided equally in Group-A (tissue adhesive Dermabond) and in Group-B (conventional suturing technique). The time required to close the wound was recorded. On 7th postoperative day wound was assessed on the basis of presence or absence of infection and wound dehiscence. Results: In patient with tissue adhesives the mean closure time was 47.32±69.13 seconds while with suture closure it was205.00±113.12 seconds. 4% patients observed to have wound infection in tissue glue versus 16% in suture closure. Wound dehiscence was found in 2% patients with wound closed by tissue glue and 14% in patient with suture closure. Conclusion: The study concluded that tissue adhesive is a safe and effective method for closure of skin incision and there is a significant difference in wound closure time, wound dehiscence and wound infection when compared with conventional suturing.